Thermostable water reservoirs in the interlayer space of a sodium hectorite clay through the intercalation of γ-aminopropyl(dimethyl)ethoxysilane in toluene. Issue 1 (13th December 2021) - Keil, Waldemar; Zhao, Kai; Oswald, Arthur; Bremser, Wolfgang; Schmidt, Claudia; Hintze-Bruening, Horst
Abstract : Thermostable compartmentalized sodium-water sites through intercalated γ-aminopropyl-dimethyl-ethoxy silane in synthetic hectorite. Abstract : Treatment of Na + -based hectorite LAPONITE® (LAP) and of Na + -montmorillonite (MMT) with a homologous series of γ-aminopropyl(methyl) x (ethoxy) y silanes ( x + y = 3, y > 0) in toluene was studied by means of thermogravimetric analysis coupled with mass spectrometry, infrared spectroscopy, 29 Si and 23 Na solid-state nuclear magnetic resonance spectroscopy and powder X-ray diffraction. The triethoxy silane (APTS) exclusively grafts on the clays' edges as branched oligomers whereas both the monoethoxy silane (APMS) and the diethoxy silane (APDS) are also intercalated, the latter as linear oligomers. Intercalation of APMS varies for MMT and LAP: MMT hosts the smallest amounts of the silanes with marginal increase of the basal distance and no stabilization of water. On the contrary, LAP accommodates the largest amount of guests in the form of monomeric APMS which yields the largest increase of the basal distance and stabilizes water up to 200 °C when APMS dimerizes. APMS stabilization is attributed to intramolecular Si–O–H–NH2 hydrogen bonds and the hydrophobic geminal methyl groups together with the trimethylene sides of the cyclic monomers are thought to compartmentalize the hydrated sodium sites. The high temperature release of water from APMS@LAP is discussed in the light of potentially triggered interphase degradation in composite materials for recycling purposes.